LBOS 01-01A COMPARISON OF THE IMPACT OF MORNING OR NIGHT DELIVERY OF ANTIHYPERTENSIVE AGENTS ON 24 HOUR ABPM LEVELS: A RANDOMISED CROSS-OVER TRIAL (HARMONY). (September 2016) - Poulter, Neil; Anjum, Aisha; Cross, Mary; Falaschetti, Emanuela; Savopoulos, Christos; Kanellos, Ilias; Szigeti, Matyas; Thom, Simon; Hatzitolios, Apostolos
Abstract : Objective: Some data suggest that nocturnal rather than daytime dosing of antihypertensive agents may have beneficial effects on consequent cardiovascular outcomes. This trial was designed to evaluate whether ABPM levels differ by timing of drug dosing, as a possible explanation for these observations. Design and Method: 103 male or female patients aged 18–80 years with "controlled" hypertension (⩽150/⩽90 mmHg) for at least three months on stable therapy of ≥1 antihypertensive agent were recruited from two centres; London and Thessaloniki. Patients were randomised to receive their usual therapy either in the morning or evening (6am-11am/6pm-11pm) for 12 weeks, then participants crossed-over to the alternative timing of drug administration for a further 12 weeks. Clinic BPs using standardised methodology and a 24 hour ABPM recording were taken at baseline, 12 and 24 weeks along with completion of the EQ-5D-5L quality of life questionnaire. The study was powered to detect 3mmHg difference in mean 24h SBP with 80% power and α = 0.05 significance level, and reached the target sample size. Regression model was used to calculate confidence intervals adjusted to centre, period (visit) and sequence (group). Results: 95 patients (92%) completed all three ABPM recordings. The mean age of recruits was 52 years and 44% were female. 24 hour systolic and diastolic BPs did not differ between daytime and nocturnal dosing (table). Similarly, there was no impact on mean daytime (7.00am–10.00pm) or night time (10pm–7.00am) ABPM levels, nor on clinic BP levels. Stratification by age (<65/≥65 years) and by gender did not affect the results. Conclusions: In patients with stable BP levels and hypertension diagnosed at least one year ago, the timing of antihypertensive drug administration (morning or evening) did not affect the mean 24 hour ABPM levels recorded.